Crosslinking and ozone degradation of thermosetting resins based on maleic anhydride/diene copolymer and polyfunctional alcohols. Issue 45 (6th August 2015) - Lou, Limin; Nagashima, Mika; Okamura, Haruyuki; Matsumoto, Akikazu
ABSTRACT Crosslinking and de‐crosslinking reactions of an alternating copolymer of maleic anhydride (MAn) and 2, 4‐dimethyl‐1, 3‐pentadiene (DMPD) by thermal curing with polyfunctional alcohols as the crosslinkers and subsequent ozone degradation are reported in this article. The ring‐opening reaction of an anhydride group by polyfunctional alcohols produces network polymers with an ester linkage. The rate of crosslinking reaction depends on the curing conditions, i.e. the structure of the used alcohols and the curing temperature and time. The crosslinking density of the alcohol‐cured copolymers is low due to a slow reaction between the anhydride and hydroxy groups, being different from the corresponding epoxy‐cured copolymer with a dense network structure reported in a previous article. The insoluble resins are readily de‐crosslinked and solubilized by ozone degradation. The polymer surface modification by ozone is also investigated. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42763.